2007
DOI: 10.1192/bjp.191.51.s63
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and paranoid ideations in people with an ‘at-risk mental state’ for psychosis

Abstract: Virtual reality is an acceptable experimental technique for use with individuals with at-risk mental states. Paranoia in virtual reality was understandable in terms of the cognitive model of persecutory delusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 25 publications
5
70
0
2
Order By: Relevance
“…In line with previous studies (Valmaggia et al, 2007;Masillo et al, 2012) we found that UHR subjects showed high sensitivity to interpersonal interaction, high vigilance to others' behaviour in an attempt to gauge their response, as well as high level of anxiety about separation from significant others. The NS group had IPSM scores similar to those reported within previous general population studies (Otani et al, 2008;Green et al, 2011) and healthy control sample (Masillo et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies (Valmaggia et al, 2007;Masillo et al, 2012) we found that UHR subjects showed high sensitivity to interpersonal interaction, high vigilance to others' behaviour in an attempt to gauge their response, as well as high level of anxiety about separation from significant others. The NS group had IPSM scores similar to those reported within previous general population studies (Otani et al, 2008;Green et al, 2011) and healthy control sample (Masillo et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…However, early studies indicated high interpersonal sensitivity and problems with self-confidence as being part of the subjective symptoms and observable behavioural changes occurring during the prodromal phase of schizophrenia (Subotnik & Nuechterlein, 1988;Häfner et al, 1992;Hambrecht et al, 1994). More recent studies have confirmed an association between interpersonal sensitivity, avoidant coping strategies, persecutory ideations and depressive symptoms in the ultra-high-risk and non-clinical samples (Valmaggia et al, 2007;Green et al, 2011;Masillo et al, 2012;Joo et al, 2012). These findings suggest that individuals who have problems in interpersonal sensitivity tend to modify their behaviour to comply with others' expectation in an attempt to minimize the risk of criticism or rejections.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Virtual Reality (VR) environment (developed by the Department of Computer Science at University College London) used in this study to assess paranoid ideation was identical to that used in previous research (Fornells-Ambrojo et al , 2008;Freeman, 2008;Valmaggia et al , 2007). The environment was designed to be perceived neutral by the majority of the general population and was a tube train ride modelled on the interior of a London Underground train carriage.…”
Section: Virtual Reality Paradigmmentioning
confidence: 99%
“…However, research using virtual reality to study in vivo and in situ reactions to social situations allows the measurement of real-time physiological activation and the assessment of thoughts, mood and symptoms as they occur(e.g. (Fornells-Ambrojo et al, 2013;Freeman et al, 2005;Freeman et al, 2003;Stinson et al, 2010;Valmaggia et al, 2007;Veling et al, 2014)). …”
Section: Introductionmentioning
confidence: 99%